Perbandingan Prestasi Belajar Siswa di SMAN 4 Kota Jambi dan SMAN 3 Muaro Jambi - Xikha Marlina Gysberthus; Rula Sakinah; Dila Wihdati; Syam Chaverlin Veniayu; Isma Ramadhani; Reski Wulan Dari; Selly Ayuni Putri; Karmila Karmila; Siti Marwiyah; Eka Anugrah Wati (Universitas Batanghari Jambi, 2023)
Learning achievement is a measure of the success or failure of an educational process. Learning achievement can also be interpreted as something that is produced or the result of an activity that is done, created both individually and in groups. Student achievement is influenced by internal factors and external factors. Learning achievement of students can be measured from the results that have been achieved by students both from internal and external factors because the evaluation results can reflect the ability of students to master the material that has been taught. These results show in the learning achievement of students at SMAN 4 Kota Jambi and SMAN 3 Muaro Jambi that each school has its own advantages, especially in the learning achievement of its students. The two schools show a significant comparison in the management of school activities. At SMAN 4 Jambi City, the non-academic achievement obtained was that one of the students had won the rank of the Indonesian under 17 national football team which would be held in mainland Europe, Turkey. This is certainly something to be proud of for the school, parents and students themselves. Meanwhile, at SMAN 3 Muaro Jambi, one of the students was selected to become PASKIBRAKA in Jambi Province